(untitled) - Ause, Wayne (Emeryville, Calif., 1996)
A freelance writer and Internet Web page creator introduces users to the wonderfully graphical World Wide Web with this step-by-step, full-color book. New Web users will find this book very useful as it leads them from beginner through intermediate aspects of the Web.
Keywords: World Wide Web,Mạng internet